1990
DOI: 10.1084/jem.171.5.1485
|View full text |Cite
|
Sign up to set email alerts
|

Acute lethal graft-versus-host reaction induced by major histocompatibility complex class II-reactive T helper cell clones.

Abstract: T cell clones isolated from class II MHC-disparate MLR combinations, and specific for I-Ak and I-Ek molecules, respectively, are shown to induce acute lethal graft-vs-host disease in unirradiated recipients. Cytolytic and noncytolytic clones are equally efficient in this respect. The lethal disease is dependent on recognition of the stimulatory class II molecules in the host. The clones home to lungs and liver, and become activated in these organs as demonstrated by an in vivo thymidine incorporation assay. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…On day 15 the lines were readjusted to 2 x 10 s ceUs/ml and were restimulated with irradiated, syngeneic, human APC (PBMC, 2 x 106/ml), CD3 mAb (1/zg/ml), and rlL-2 (10 ng/ml) in 24-well plates in 2 ml DMEM-FCS medium per well. Thereafter, the cells were fed weekly with fresh DMEM-FCS medium containing rib2 (10 ng/ml) and restimulated with syngeneic, human APC and Ag (CD3 mAb) once a month according to the protocol previously described (19).…”
Section: T Cell Proliferation Assay With Cells Freshly Prepared From mentioning
confidence: 99%
“…On day 15 the lines were readjusted to 2 x 10 s ceUs/ml and were restimulated with irradiated, syngeneic, human APC (PBMC, 2 x 106/ml), CD3 mAb (1/zg/ml), and rlL-2 (10 ng/ml) in 24-well plates in 2 ml DMEM-FCS medium per well. Thereafter, the cells were fed weekly with fresh DMEM-FCS medium containing rib2 (10 ng/ml) and restimulated with syngeneic, human APC and Ag (CD3 mAb) once a month according to the protocol previously described (19).…”
Section: T Cell Proliferation Assay With Cells Freshly Prepared From mentioning
confidence: 99%
“…49,50 However, these cells engage in recirculation after 5-7 days. 51,52 This might be the reason why we did not detect ex vivo CD8 ϩ T cells that would produce increased levels of PFN. The PFN-producing cells that can be detected in the blood might have encountered antigen more than 5 days before testing, but still in the recent past.…”
Section: Fig 3 Hiv Peptides Induced Pfn Secretion In Pbmcs and Cd8 mentioning
confidence: 66%
“…To induce acute lethal GVHD in unirradiated recipients, certain strain combinations of MHC class I + IT-disparity and relatively large numbers (108) of donor cells are required (Rolink et al, 1983). Recently, Lehmann et al (1990) demonstrated that alloreactive T cell clones can induce acute lethal GVHD in unirradiated recipients with single MHC disparity after i.v. injection of 5 x 106-107 cells.…”
Section: Discussionmentioning
confidence: 99%